MAGNETIC RESONANCE CHOLANGIOPANCREATOGRAPHY UNCOVERING A RARE BILE DUCT STENOSIS LEADING TO HEPATIC ENCEPHALOPATHY: A CASE REPORT - Setyawan, Gratia Enggar; Dermoredjo, Sutaryanu (Department of Radiology, Medical Faculty, University of Brawijaya, 2026)
Common bile duct (CBD) biliary stricture is an uncommon but clinically significant cause of chronic cholestasis and hepatic dysfunction that may progress to hepatic encephalopathy (HE). Identification of biliary obstruction as the reversible etiology of HE is crucial for appropriate management. Magnetic Resonance Cholangiopancreatography (MRCP) is a non-invasive imaging modality with high diagnostic accuracy for evaluating biliary pathology without contrast administration or ionizing radiation. We report a 47-year-old woman presenting with recurrent confusion, progressive jaundice, and significant weight loss, with a history of previous biliary surgery. MRCP demonstrated marked dilatation of the common bile duct and absence of choledocholithiasis, consistent with postoperative CBD biliary stricture. The patient developed recurrent hepatic encephalopathy secondary to chronic cholestasis and hepatic dysfunction. Surgical revision of the bilodigestive shunt resulted in clinical stabilization and improvement. This case highlights the essential role of MRCP in identifying biliary stricture as a treatable cause of hepatic encephalopathy and guiding definitive surgical management.